Implementasi GeoGebra pada Pembelajaran Matematika Tingkat SMA/SMK - Aulia Nisa Trisna Ihsani (Papanda Publisher, 2025)
This study aims to examine the learning conditions that influence the effectiveness of GeoGebra in mathematics learning. The research employed a Systematic Literature Review (SLR) method by analyzing empirical research articles obtained from the Google Scholar database published between 2019 and 2025. The selected articles focused on the use of GeoGebra in mathematics learning contexts. The findings indicate that the effectiveness of GeoGebra is not automatic but highly dependent on the learning conditions in which it is implemented. GeoGebra tends to be more effective when applied to visually oriented mathematical topics, particularly geometry and trigonometry, and when integrated into student-centered learning designs supported by instructional methods that encourage exploration and interaction. These findings suggest that the use of GeoGebra as a learning medium should be accompanied by appropriate instructional planning to optimally enhance students’ conceptual understanding of mathematics.